Effects of Sports Participation on Academic Performance in Adolescents - Nguri, Moses (American Journal of Recreation and Sports, 2024)
Purpose: The aim of the study was to assess the effects of sports participation on academic performance in adolescents. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicate a positive correlation between sports involvement and academic achievement, others highlight potential drawbacks such as time constraints and fatigue. Sports participation has been associated with improved cognitive function, time management skills, and self-discipline, which can positively impact academic performance. However, excessive commitment to sports may lead to neglect of academic responsibilities and increased stress. Furthermore, the influence of sports on academic performance can vary depending on factors such as the type of sport, level of competition, and individual characteristics of the student. Overall, while sports participation can offer various benefits for adolescents, striking a balance between athletic and academic pursuits is crucial for maximizing overall development and success. Implications to Theory, Practice and Policy: Self-determination theory, social learning theory and achievement goal theory may be used to anchor future studies on assessing effects of sports participation on academic performance in adolescents. Educators and school administrators should prioritize the integration of physical activity and sports programs within school curricula to support academic success. Policymakers should recognize the importance of sports participation in promoting holistic youth development and academic success.